2019
DOI: 10.1063/1.5094628
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure properties of CuZn2InTe4 and AgZn2InTe4 quaternary chalcogenides

Abstract: Quaternary chalcogenides composed of earth-abundant and primarily nontoxic constituents are currently being explored for thermoelectric applications. The representatives of this class, CuZn2InTe4 and AgZn2InTe4, have been synthesized, and here, we present a comparative study of their structure–property relations using first principles simulations. Our calculations show that the lattice structure for both materials is very similar in terms of characteristic atomic distances and lattice structures, which compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Recent experiments have shown that CuZn 2 InSe 4 , CuZn 2 InTe 4 , CuCd 2 InTe 4 , CuMn 2 InTe 4 , and AgZn 2 InTe 4 have low thermal conductivity. 11–21 These results are consistent with the low measured thermal conductivity for related systems such as Cu 2 ZnSnS 4 and Cu 2 CdSnSe 4 , which belong to the widely studied class I 2 –II–IV–VI 4 (I = Cu, Ag; II = Cd, Zn, Ca, Co, Fe, V; IV = Si, Sn, Ge; VI = S, Se, Te). 22,23 The close connection between I–II 2 –III–VI 4 and I 2 –II–IV–VI 4 is also evident in the similar structural phases these materials can have.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recent experiments have shown that CuZn 2 InSe 4 , CuZn 2 InTe 4 , CuCd 2 InTe 4 , CuMn 2 InTe 4 , and AgZn 2 InTe 4 have low thermal conductivity. 11–21 These results are consistent with the low measured thermal conductivity for related systems such as Cu 2 ZnSnS 4 and Cu 2 CdSnSe 4 , which belong to the widely studied class I 2 –II–IV–VI 4 (I = Cu, Ag; II = Cd, Zn, Ca, Co, Fe, V; IV = Si, Sn, Ge; VI = S, Se, Te). 22,23 The close connection between I–II 2 –III–VI 4 and I 2 –II–IV–VI 4 is also evident in the similar structural phases these materials can have.…”
Section: Introductionsupporting
confidence: 80%
“…The compound CuZn 2 InSe 4 belongs to the I–II 2 –III–VI 4 class of materials, which is similar to I 2 –II–IV–VI 4 quaternary chalcogenides as both types of system are derivatives of the simpler binary II–VI zincblendes. The five structural phases for CuZn 2 InSe 4 can also be found for other representatives of both I–II 2 –III–VI 4 and I 2 –II–IV–VI 4 , 13,45 although the dynamical stability, electronic and vibrational properties, and associated transport behaviors depend on the particular chemical composition. Here applying first-principles simulations we study in depth the ST, KS, PMCA, WKS, and WST CuZn 2 InSe 4 for their structure–property relations.…”
Section: Discussionmentioning
confidence: 99%
“…[5] More recently, the synthesis and physical properties of ternary [6,7] and quaternary [8][9][10][11] chalcogenides have been of intense interest, not only due to an interest in their fundamental properties but also for applied research toward energy-related applications. [12][13][14][15][16] For certain materials, the electrical properties can be modified by a variation in stoichiometry, [17][18][19] while others display transport properties that are atypical of compositions in this class of materials. [20,21] Wide bandgap semiconductor chalcogenides continue to be of interest due to their interest in a broad range of technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 Recently, quaternary chalcogenide systems such as CuZn 2 InTe 4 , CuMn 2 InTe 4 and AgZn 2 InTe 4 , with an electronic direct bandgap around 1 eV, has been reported in the bulk regime with a cubic zinc blende structure. [44][45][46][47] In this study, we report the synthesis and characterization of novel quaternary Cu doped Zn-In-Te QDs with the composition CuZn 2 InTe 4 . The QDs were synthesised via green routes 31,[33][34][35][36] by employing a heterogeneous suspension of Te in octadecene (ODE) and oleylamine (OLA) as the Te green precursor and dodecanethiol (DDT) as the capping ligand.…”
Section: Introductionmentioning
confidence: 99%